2015
DOI: 10.1002/ijc.29487
|View full text |Cite
|
Sign up to set email alerts
|

Association between height and thyroid cancer risk: A meta-analysis of prospective cohort studies

Abstract: While several epidemiological studies have investigated the relationship between height and risk for thyroid cancer, the results were inconsistent. In the present study, a systematic review and meta-analysis of prospective cohort studies was conducted to assess the impact of height on thyroid cancer risk. Online databases were searched up to December 30, 2014, for prospective cohort studies on the association between height and thyroid cancer risk. Pooled relative risks (RRs) and 95% confidence intervals (CIs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…We also found that maternal height was positively associated with higher risk of thyroid cancer overall and both papillary and follicular subtypes. This finding is consistent with previous studies reporting that taller children 4 or adults 5 have a modestly increased risk of thyroid cancer in adulthood. However, we found no association between adult weight or BMI and risk of thyroid cancer, consistent with a previous study of Swedish men, 41 but in contrast to a number of studies in other populations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that maternal height was positively associated with higher risk of thyroid cancer overall and both papillary and follicular subtypes. This finding is consistent with previous studies reporting that taller children 4 or adults 5 have a modestly increased risk of thyroid cancer in adulthood. However, we found no association between adult weight or BMI and risk of thyroid cancer, consistent with a previous study of Swedish men, 41 but in contrast to a number of studies in other populations.…”
Section: Discussionsupporting
confidence: 93%
“…2 In most countries, known risk factors such as ionizing radiation and genetic syndromes account for a minority of cases, 3 which has prompted investigations of other factors that potentially could facilitate the identification of high-risk subgroups. A number of studies have reported that increased height or body mass index (BMI) in either childhood 4 or adulthood [5][6][7][8][9][10] is associated with a modestly increased risk of adult thyroid cancer, possibly related to growth factor pathways involving insulin-like growth factor I (IGF-I). 11,12 IGF-I is known to have procarcinogenic properties and to be produced locally in thyroid cancer cells.…”
mentioning
confidence: 99%
“…Because height is used to calculate BMI and has been associated with PTC risk in previous studies 29,30 , we also repeated all analyses using sex-specific quartiles of height as an independent variable.…”
Section: Discussionmentioning
confidence: 99%
“…The association between height and thyroid cancer incidence could be explained partially by the effect of insulin-like growth factor (IGF-1). Previous studies reported a positive association between the level of IGF-1 and the risk of thyroid cancer incidence [1,26]. Higher IGF-1 levels promote mutation in various cell lines including thyroid cells [1,21,26,27] and contribute to increased risk of cancer incidence by stimulating cell proliferation, adhesion, and migration, and by inhibiting apoptosis [1, Thyroid Cancer and Anthropometric Factors in the Japanese Population J. Sado et al 21,27].…”
Section: Discussionmentioning
confidence: 99%